The perception of individual taxpayers against the intention of using e-form services - Tapi Omas Annisa; Noorlailie Soewarno; Isnalita Isnalita (Faculty of Economics and Business Mulawarman University, 2019)
This study aims to examine the perception of individual taxpayers against the intention of using e-form services. This research uses UTAUT model which is based on 4 main constructs which are Performance expectancy, effort expectancy, social influence and facilitating condition. Methods of data collection using online or manual questionnaires. The sample of research is individual taxpayers as much as 100 respondents. Data analysis using Structure Equation Model with Smart PLS 3.0 software. The results showed that Performance expectancy, effort expectancy, and social influence have no significant relationship whereas facilitating condition has a significant relationship.